The worldwide incidence of preterm birth: a systematic review of maternal mortality and morbidity - Beck, Stacy (World Health Organization, 2010)
OBJECTIVE: To analyse preterm birth rates worldwide to assess the incidence of this public health problem, map the regional distribution of preterm births and gain insight into existing assessment strategies. METHODS: Data on preterm birth rates worldwide were extracted during a previous systematic review of published and unpublished data on maternal mortality and morbidity reported between 1997 and 2002. Those data were supplemented through a complementary search covering the period 2003–2007. Region-specific multiple regression models were used to estimate the preterm birth rates for countries with no data. FINDINGS: We estimated that in 2005, 12.9 million births, or 9.6% of all births worldwide, were preterm. Approximately 11 million (85%) of these preterm births were concentrated in Africa and Asia, while about 0.5 million occurred in each of Europe and North America (excluding Mexico) and 0.9 million in Latin America and the Caribbean. The highest rates of preterm birth were in Africa and North America (11.9% and 10.6% of all births, respectively), and the lowest were in Europe (6.2%). CONCLUSION: Preterm birth is an important perinatal health problem across the globe. Developing countries, especially those in Africa and southern Asia, incur the highest burden in terms of absolute numbers, although a high rate is also observed in North America. A better understanding of the causes of preterm birth and improved estimates of the incidence of preterm birth at the country level are needed to improve access to effective obstetric and neonatal care.